THE EFFECTS OF CONTROLLED SKIDDING TECHNIQUE ON RESIDUAL STAND DAMAGE AND GROUND EXPOSURE IN SWAMP FOREST LOGGING - Sona Suhartana (Secretariat of Agency for Standardization of Environment and Forestry Instruments, 2004)
The case study was carried out at a swamp forest company in Riau in 2001. The aim of the study was to determine the effect of controlled skidding technique to residual stand damage and ground exposure. Data collected includes: felled trees, poles, trees with the diameter 20 cm up, damaged poles, damaged trees and ground exposure. The data was analyzed with t-test. The study showed the following results:The average of residual stand damage caused by controlled skidding technique was 29.05% for poles and 19.8% for trees. The average of residual stand damage caused by conventional skidding technique was 34.2% for poles and 24.9% for trees. The difference of 5.1% (poles) and 5.1 % (trees) were significant at 95%.The average of ground exposure caused by controlled skidding technique and conventionalskidding technique was respectively 16.06% and 18.4%. The difference of 2.34% was significant at 95%.